The Mediating Role of Rape Myths in the Relationship Between the Use of Hentai Pornography and Sexually Aggressive Strategies: A Study with College Students - Almeida, Beatriz (Journal of interpersonal violence, 2025)
The current study aims to test the hypothetical link between hentai pornography use, rape myths endorsement, and sexually aggressive strategies. Furthermore, it aims to capture if such a trajectory echoes across gender and human-realistic pornography. The work targeted a sample of 906 college students, of whom 533 were men and 373 were women, who completed an online survey to capture pornography use, rape myths, and sexually aggressive behavior. Participation criteria included being heterosexual, over 18, pursuing higher education, and using hentai pornography. The results revealed that the frequency of hentai pornography use predicts sexually aggressive behaviors in male and female participants. The endorsement of rape myths mediated the relationship between the frequency of hentai use and sexually aggressive behavior in both genders and the relationship between the intensity of hentai use and sexually aggressive behavior in men. When considering human-realistic pornography, it was found that the frequency of use predicts sexually aggressive behavior in female participants. The endorsement of rape myths mediated the relationship; no other relationship was found. This work aims to increase awareness about the implications of using hentai and human-realistic pornography and highlight the importance of sexual violence prevention in the college setting.